Serological based monitoring of a cohort of patients with chronic chagas disease treated with benznidazole in a highly endemic area of Northern Argentina - Niborski, Leticia Laura (2016)
This study aimed to evaluate well-documented diagnostic antigens, named B13, 1F8 and JL7 recombinant proteins, as potential markers of seroconversion in treated chagasic patients. Prospective study, involving 203 patients treated with benznidazole, was conducted from endemic areas of northern Argentina. Follow-up was possible in 107 out of them and blood samples were taken for serology and PCR assays before and 2, 3, 6, 12, 24 and 36 months after treatment initiation. Reactivity against Trypanosoma cruzi lysate and recombinant antigens was measured by ELISA. The rate of decrease of antibody titers showed nonlinear kinetics with an abrupt drop within the first three months after initiation of treatment for all studied antigens, followed by a plateau displaying a low decay until the end of follow-up. At this point, anti-B13, anti-1F8 and anti-JL7 titers were relatively close to the cut-off line, while anti-T. cruzi antibodies still remained positive. At baseline, 60.8% (45/74) of analysed patients tested positive for parasite DNA by PCR and during the follow-up period in 34 out of 45 positive samples (75.5%) could not be detected T. cruzi DNA. Our results suggest that these antigens might be useful as early markers for monitoring antiparasitic treatment in chronic Chagas disease.